Spectroscopy for Questioned Documents Examination: Case Study of Suprasl Abbey‘s Chancery - Žižiūnas, Tadas (Knygotyra, 2018)
[full article and abstract in Lithuanian; abstract in English]The aim of the article was to create a research methodology for questioned historical documents where UV-VIS-NIR reflectance spectroscopy is used to identify color variations of historical documents written with iron gall ink. Such methodology was introduced because most historical documents are written with iron gall ink. Secondly, iron gall ink is causing various damage to historical documents hence new and effective research methods are needed. Thirdly, such new methodologies should be accessible for humanities and social science where no specific chemical knowledge is needed.20 volumes of Supraslis abbey office’s historical documents were selected as a case study to test the created methodology. Each book was numbered and labeled with the known provenance. In each book three pages (in the beginning, in the middle and in the end) were selected and two measurements (in the top of the page and in the end) were taken. Also so called Q page (questioned) was de visu selected as different from other pages which turned out 79% not being thecase. What is more, all measurement’s exact spots were also micro- photographed and macro – photographed to make sure that the measured ink samples that were selected had no stains, were not damaged or otherwise polluted. Measurements were performed with CRAIC PV 308 spectrophotometer calculating 900 measurements average for one value of ∼1mm2 sample area.The case study demonstrated that UV-VIS-NIR reflectance spectroscopy can be a very fast and nondestructive tool to investigate historical questioned documents, certain pages of a documenet or even to compare several books from the same or different time periods and place origin. However, effective research require ink color comparison with color maps or other mathematical representation models (e.g. MacAdam’s ellipse). Furthermore, for more precise comparison, big databases with books, origin dates, origin place, spectral data, physical condition and other related parameters are needed.
Keywords: falsification, UV-VIS-NIR spectroscopy, heritage, iron gall ink, questioned documents, methodology, interdisciplinary research